Performance Art Antara Media Penyadaran, Kepentingan Pasar Dan Partisipasi International - Isnanta, Satriana Didiek (Institut Seni Indoensia Surakarta, 2012)
Good performance art is work that managed to amaze the public. Successfully influenced public to observe every detail. Instead, the public will demand the uniqueness of the event that makes it willing to pay attention to the performance, detailed for detailed. From the above explanation affirmation finally appeared a question, when a performance art relies heavily once with the right choice of space and how the public (audience or the audience), thus creating a unique event and can amaze the public. In the video performance, no other consciousness to show more conceptual performance: performance scene that has been designed, presented in video media. May be more readily as experimentation on attempted filmed theater, but completely abandoned the live performance itself, because of the possibility of a repetition of the scene to be there. As an avant-garde art (avant garde) as described above,â€ originalityâ€ and the seriousness of the challenges of performance art gets a modern capitalist society. Performance art that was originally to be agents of change in the value of the community, the are deflected by spearheading the advertising to market interests.Â keywords : performance art, agent of change, ambient media